International conference on financial cycles, systemic risk, interconnectedness, and policy options for resilience overview and summary of papers. (Asian Development Bank, 2017)
Jointly organized by the ADB Economic Research and Regional Cooperation Department and the Institute of Global Finance - University of New South Wales, the conference gathered leading academics, central bankers and financial regulators, and international financial organizations and discussed the theory, practices, and policy implications of financial interconnectedness for systemic risk and financial stability.